Effect of ZnO twin grain boundary on Zn vacancies induced d0 ferromagnetism: First‐principles calculations. Issue 6 (17th February 2017) - Wu, Jingjing; Tang, Xin; Long, Fei; Tang, Biyu
Abstract : First‐principles calculation, based on density functional theory, is applied to study the electronic and magnetic properties of Zn vacancies in ZnO Σ7 (12 3 ¯ 0) twin grain boundary with fivefold coordination sites. The fivefold coordination can facilitate the formation and aggregation of Zn vacancies. The O atoms around Zn vacancies are responsible for the ferromagnetic state, which has an obvious character of d 0 ferromagnetism. Meanwhile, the twin grain boundaries have a two‐dimensional periodic structure, and periodical fivefold coordination sites are available, which favors the realization of the macroscopic ferromagnetic ordering. The result also gives us a new thinking to understand d 0 ferromagnetism in undoped ZnO.